Optimal Placement and Sizing of Distributed Generators Based on Equilibrium Optimizer - Zhang, Weiwei; Wang, Shuliang (Frontiers in Energy Research, 2022)
To solve the problems of environmental pollution and energy consumption, there is an urgent need to develop clean and renewable energy to maintain the sustainable development of society. Therefore, distributed generation (DG) has attracted engineers’ extensive attention. However, DG output of is usually random and intermittent. When connected to different locations, different sizing, and different distribution networks, it will have varying impact on the safe and stable operation of the power system. When choosing the optimal DG access scheme, planners must consider the impact of size, type, and location to ensure that power grid operation is safe, stable, reliable, and efficient. Therefore, this article proposes an objective function considering power losses, voltage profile, and pollution emission, which is solved by equilibrium optimizer (EO). Finally, the effectiveness of the proposed strategy is verified based on IEEE 33 and 69-bus distribution networks. The results show that the strategy can effectively improve the pollution emission of the system, effectively reduce power loss, and improve the voltage profile.